The Community Management Strategies in the Jaga Hutan Borneo Program in Martadinata Village - Ayu Malinda, Revi; Yedo Kurniawan; Oxsi Purbaya (Prospect Publishing, 2024)
The reduction of carbon emissions has gained increasing attention in Indonesia, particularly in the industrial regions of Kalimantan Island. The Martadinata Village Forest, which directly borders the operational area of PT Pertamina Gas Operation Kalimantan Area, is now under threat due to the prevalence of illegal logging activities. The natural ecosystem, water resources, and vegetation within the Kutai National Park conservation area have become targets of irresponsible illegal actions. Through the Jaga Hutan Borneo program, PT Pertamina Gas Operation Kalimantan Area, in collaboration with the Village Government, TNK (Kutai National Park), the Kampung Bersama Tourism Awareness Group, and the Forum for Environmental Care, initiated a program aimed at preserving the ecology of the Martadinata forest through sustainable tourism. This tourism development strategy is implemented using a multi-stakeholder approach, focusing on forest conservation, environmental education, and the promotion of environmentally friendly alternative economic activities. The program not only protects carbon absorption areas but also empowers the community through conservation-based economic initiatives